In vitro streptozotocin model for modeling Alzheimer-like changes: effect on amyloid precursor protein secretases and glycogen synthase kinase-3 - Plaschke, Konstanze; Kopitz, Jürgen (Journal of neural transmission, 2015)
There is accumulating evidence for a pathogenetic link between sporadic Alzheimer’s disease (AD) and diabetes mellitus (DM). At subdiabetogenic doses, the cerebral administration of the diabetogenic substance streptozotocin (STZ) induces an insulin-resistant brain state (IRBS). The aim of the present pilot study was to investigate the effect of STZ on Alzheimer-like characteristics such as amyloid precursor protein (APP) cleavage secretases, betaA4 fragment, and glycogen synthase kinase (GSK) in vitro. Different STZ concentrations (0-5 mM) and incubation intervals (0-48 h) were tested to find appropriate cell culture conditions for further biochemical analyses in human neuroblastoma cells (SK-N-MC). Lactate dehydrogenase (LDH) was measured spectrophotometrically. Intracellular ATP was determined using bioluminescent luciferase assay. Secretase activity (alpha, beta, and gamma) was measured by employing commercial fluorometric secretase activity assay kits, betaA4 fragment by immunoprecipitation. Glycogen synthase kinase-3alpha/beta (total and phospho-GSK) content was assayed by ELISA technique. In vitro STZ administration (1 mM) induced a significant reduction in intracellular ATP concentration without pronounced cell death after 24 and 48 h as measured by LDH. Under these experimental conditions, a significant increase in beta-secretase and a significant drop in alpha-secretase were obtained, whereas gamma-secretase was not changed significantly. Simultaneously, the betaA4 concentration was increased by about threefold. Furthermore, STZ significantly increased total GSK and markedly decreased phospho-GSK. A direct link between STZ, intracellular ATP deficit, and Alzheimer-related enzymes was shown in this in vitro pilot study. Thus, these results support the hypothesis that sporadic AD is being recognized as an IRBS, which can be modulated by in vitro STZ model. Continuing investigations relating pathogenetic mechanisms and AD-like hallmarks are necessary to modulate different cascades of the IRBS using in vitro models.
Published online: 5 October 2014
Gesehen am 08.07.2020